Food products in two cosmetic formulations: determination of the stability and toxicity - Martins, Vitor Manuel Ramalheira (2018)
The cosmetic market is extending to millions of consumers worldwide and its industry is worth tens of billions of US$ [ ]. The competitive environment and the demands made by the consumers pushed the manufactures to develop new types of cosmetic products and to use new ingredients, such as bee products, to produce formulations with higher quality and efficacy. The aim of this work was to develop two cosmetic formulations for topical application that combine bee products and essential oils from medicinal plants, as well it was to extract and analyse the essential oils of an edible wild mushrooms Clitocybe odora (Buli.) P. Kumm, grown in vitro, to understand the potential of it, as a source of bioactive compounds usable in cosmetics. The effect of two different bee products (hydroalcoholic exti-act of propolis and two honeys of Lavandula ssp. with different geographic provenance) and essential oils from two different species (Thymus Zygis L. subsp. Zygis and Mentha pulegium L.) was tested. For that purpose, several preparations were elaborated to witch one essential oil and a bee product were added. For each type of formulation, one preparation with essential oils but without a bee product was also prepared. In relation to the bee products, the Lavandula spp. honey was used in the proportion of l :50 (v/m) and l :20 (v/m); the hydroalcoholic extract of propolis, using ethanol, was add in a concentration of5% (m/v). The concentration of essential oil used was 7. 86x10^g/g (e. o./ emulsion). Additionally was also tested the toxicity of the two essential oils and the Clitocybe odora volatiles, through the LD50 determination, using Artemia Salina L.. To determine the effect of the bee products in the formulations stabilization were made physicochemical tests and stabilization tests. Was not verified alterations m the relative density of the samples, in the pH or in a vibration test made placing the samples 10 seconds in the vortex. When the samples were place during l 5 days in a daylight lamp, was observed, by comparing with samples just with essential oil in the same conditions, that all the samples with propolis extract changed the colour and the odour. The effect of the bee products in the viscosity of the formulations was also tested. When using a lower spindle rotation velocity, the use of the honey from the North of Portugal and of the propolis extract increased the viscosity of the emulsions. Both the two essential oils tested as the in vitro Clitocybe odora volatiles show to have a LD50<0,1 mg/ml.